2011
DOI: 10.2190/pm.42.3.f
|View full text |Cite
|
Sign up to set email alerts
|

A Spirituality Teaching Program for Depression: A Randomized Controlled Trial

Abstract: The Spirituality Program significantly reduced depression severity and increased response and remission rates. This non-drug treatment program should be investigated further as a treatment option for depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…The early stage of this evaluation warranted a pilot study with a design that precluded the inclusion of a comparison placebo arm. We also opted to use a waitlist trial design given its advantages [ 30 , 41 ], particularly in relation to psychotherapeutic interventions. However, it is important to recognize that concerns have been raised in the research community regarding the potential for over estimation of intervention effects using such a design [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The early stage of this evaluation warranted a pilot study with a design that precluded the inclusion of a comparison placebo arm. We also opted to use a waitlist trial design given its advantages [ 30 , 41 ], particularly in relation to psychotherapeutic interventions. However, it is important to recognize that concerns have been raised in the research community regarding the potential for over estimation of intervention effects using such a design [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Steffen et al also have reported that spirituality is a strong factor in helping women deal with menopausal symptoms ( 24 ). Several other studies also have confirmed the positive effects of spiritual intervention on postmenopausal women ( 25 ) and depressed patients ( 26 , 27 ). Although not studying postmenopausal women, Ghahari et al investigated the effects of cognitive-behavioral and spiritual-religious interventions on anxiety and depression in women with breast cancer and reported that such interventions had no effect on depression ( 28 ).…”
Section: Introductionmentioning
confidence: 69%
“…We were going to study the longterm outcomes of spiritual education. Given that many factors can affect anxiety and depression, it was not possible to control and monitor them, as previous studies showed that the effects of education decreased after eight weeks (40). Therefore, four weeks after intervention were consid-ered as the appropriate time for measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Zamaniyan et al (28) reported the effectiveness of spiritual group therapy in enhancing the quality of life and the psychological well-being of patients with breast cancer. In addition, Rickhi et al (40) found that their spirituality education program significantly reduced the depression severity and increased the depression response and remission rates during a six-month follow-up period. The response rate in their study was as high as 56% -64% (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation